"Dear Doctor, greetings of the day!": A 1-year observational study of presumed predatory journal invitations - Christos Livas; Konstantina Delli (SpringerOpen, 2023)
Abstract Background This study aimed at investigating the predatory publishing phenomenon in orthodontics by analyzing the content of unsolicited e-mail invitations received within 12 months. Methods All electronic invitations for manuscript submission, review and editorial membership received between 1 October 2021 and 30 September 2022 were collected from an orthodontist's inbox. The following data were recorded for each e-mail: date, journal title and origin, requested contribution, e-mail language, relevance to the researcher's discipline, journal characteristics (claimed metrics, editorial services, article types accepted, and publication fees), journal/publisher contact information and online presence. Journal/Publisher legitimacy and publishing standards were evaluated by listing in the Beall's list of potential predatory journals and publishers, the Predatory Reports of Cabell's Scholarly Analytics, and the Directory of Open Access Journals. Results A total of 875 e-mail invitations deriving from 256 journals were retrieved within the observation period, with most of them soliciting article submissions. More than 76% of the solicitations originated from journals and publishers included in the blocklists used in the study. Salient features of predatory journals like flattering language, abundant grammatical errors, unclear publication charges and wide variety of article types and topics accepted for publication were confirmed for the examined journals/publishers. Conclusions Nearly 8 out of 10 unsolicited e-mail invitations sent to orthodontists for scholarly contribution may be related to journals suspicious for publishing malpractices and suboptimal standards. Excessive flattering language, grammatical errors, broad range of submissions, and incomplete journal contact information were commonly encountered findings. Researchers in orthodontics should be alert to the unethical policies of illegitimate journals and their harmful consequences on the scientific literature.